2023
DOI: 10.3389/fimmu.2023.1137069
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale antibody immune response mapping of splenic B cells and bone marrow plasma cells in a transgenic mouse model

Xiaoli Pan,
Sheila N. López Acevedo,
Camille Cuziol
et al.

Abstract: Molecular characterization of antibody immunity and human antibody discovery is mainly carried out using peripheral memory B cells, and occasionally plasmablasts, that express B cell receptors (BCRs) on their cell surface. Despite the importance of plasma cells (PCs) as the dominant source of circulating antibodies in serum, PCs are rarely utilized because they do not express surface BCRs and cannot be analyzed using antigen-based fluorescence-activated cell sorting. Here, we studied the antibodies encoded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Because clonal abundances tend to correlate with affinity, the incorporation of clonal frequency rankings offers an indirect strategy for predicting Ab affinities. For instance, this was successfully demonstrated by Pan et al where the authors isolated bone marrow from immunized mice followed by Ab repertoire deep sequencing analysis [62]. Post computational screenings, they were able to effectively identify the distinct molecular features from antigen-specific clonal lineages.…”
Section: Heightened Characterization Of Absmentioning
confidence: 99%
See 2 more Smart Citations
“…Because clonal abundances tend to correlate with affinity, the incorporation of clonal frequency rankings offers an indirect strategy for predicting Ab affinities. For instance, this was successfully demonstrated by Pan et al where the authors isolated bone marrow from immunized mice followed by Ab repertoire deep sequencing analysis [62]. Post computational screenings, they were able to effectively identify the distinct molecular features from antigen-specific clonal lineages.…”
Section: Heightened Characterization Of Absmentioning
confidence: 99%
“…Moreover, they also implemented calculations associated with enrichment rankings of the various Ab frequencies to effectively identify lead candidate Abs. Notably, when experimentally validated, all top-ranking identified clones proved to be selective for the target antigen and displayed high affinities [62]. Thus, the work presented by Pan et al successfully demonstrated that the application of deep sequencing-based clonal rankings can effectively formulate affinity predictions; this is accomplished by performing frequency cross-comparisons among the various clones.…”
Section: Heightened Characterization Of Absmentioning
confidence: 99%
See 1 more Smart Citation
“…Various organs, such as the spleen, lymph nodes, bone marrow, and blood, can be accessed, each displaying differences in antibody repertoire present in ASCs and MCs. [34][35][36] The quantity and quality of the induced repertoire in immunized animals highly depend on factors such as the chosen immunization protein (antigen), its quality, dose, administration, mouse strain, genetic model, harvest time, and immunization scheme, necessitating optimization for efficient and optimal screening 37,38 (unpublished data), but the frequency of antigen specificity in total cells is usually higher than in humans. Nevertheless, appropriately chosen conditions can lead to identifying high-affinity antibodies, as the affinity distribution tends to follow a normal distribution with outliers in the highaffinity range.…”
Section: Screening An Antibody Repertoire For Candidatessingle-cells ...mentioning
confidence: 99%